The Effect of Audiolyfe Stimulation on Cognitive Development (Intelligence, Memory, and Learning Motivation in Children) in Banda Aceh - Fathiyah Ma'ani (Green Publisher Indonesia, 2026)
Cognitive development is a crucial aspect of a child's growth, encompassing thinking skills, memory, and learning motivation. This study aims to analyze the impact of Audiolyfe stimulation on the cognitive development of children aged 0–12 years in Banda Aceh, focusing on enhancing intelligence, memory, and learning motivation. A quasi-experimental method was employed with 20 children as participants. Data were collected through observation and questionnaires and analyzed descriptively. The results revealed that Audiolyfe significantly influenced children's cognitive development. Children who received this stimulation demonstrated increased intelligence, improved memory, and higher learning motivation compared to the control group. The effectiveness of Audiolyfe is attributed to the impact of sound waves on neurological activity in the auditory cortex and memory areas of the brain. Additionally, Banda Aceh's local culture—such as the tradition of listening to stories and traditional music—reinforced children's positive responses to this stimulation. This study concludes that Audiolyfe is an innovative and effective approach to supporting children's cognitive development. It is recommended that Audiolyfe be integrated into formal and informal education programs in Banda Aceh to optimally improve children's learning quality.